NON COMPLIANCE TAX ATTITUDE IS CONSIDERED UNACCEPTABLE IN SMALL BUSSINES - Indrawati Yuhertiana; Rina Moestika S; Sri Hastuti; Siti Sundari (Akuntabilitas, 2015)
Small bussines provide a major economic contribution to society and the state. Thissector have been survived Indonesia from 1998 financial crisis. There are significantcontribution to Indonesia economic. One global issues for government today is combating taxevasion. Related this issue, this research explore Indonesia small bussines community’sperception towards tax compliance.The research aims to establish whether small bussinescompany view the depth understanding of tax compliance and non compliance. It is explorethe reason being compliance and also their intention being non compliance including taxevasion and tax avoidance. It also aims to establish whether a relationship exists betweencitizens' attitudes towards tax evasion and their demographic characteristics. A survey wasundertaken in an owner of small trader in Bangkalan city, East Java Province. Qualitativeresearch is conduct to gain rich data in interpretive paradigm. The survey found that noncompliance tax attitude is considered unacceptable. In case they didn’t report their taxobligation, it is related to their lack of accounting knowledge.DOI: 10.15408/akt.v8i2.2765